The Activity Concentrations and Radium Equivalent Activity in Soil Samples Collected from the Eastern Part of Basrah Governorate in Southern Iraq - Rasha S. Ahmed; Raghad S. Mohammed; Rana O. Abdaljalil (International Journal of Analytical Chemistry)
Clay soil samples (0, 30, and 60 cm depths) were collected from two districts (Abu Al Khasib and Ad Dayr) in Basrah governorate in southern Iraq for gamma-ray spectroscopy. The activity concentrations for natural existing radionuclides in 18 soil samples were measured using high-purity germanium detector HPGe. From the obtained results of γ-ray spectroscopy, the 238U activity concentrations were found to be ranging from 2.4 to 5.6 ppm with an average of 3.5 ppm in Abu Al Khasib and ranging from 2.1 to 4.5 ppm with an average of 2.9 ppm in Ad Dayr. 232Th concentrations were ranging from 3.6 to 7.5 ppm with an average of 4.7 ppm in Abu Al Khasib and ranging from 3.7 to 7.9 ppm with an average of 5.0 ppm in Ad Dayr. 40K concentration was ranging from 0.1% to 2.0% with an average of 1.2% in Abu Al Khasib and ranging from 0.9% to 1.8% with an average of 1.3% in Ad Dayr. High 238U and 226Ra concentration levels were recorded in both study regions. The concentrations of 232Th are within the normal limits in both regions. High levels of 40K were recorded in some locations. Generally, in most locations, 40K activity was within normal ranges. The radium equivalent activity, the external hazard index, the internal hazard index, and the radioactivity level index were calculated to estimate the radiation hazard in Basrah. The estimated radiation hazard indices were within normal limits, except the radioactivity level index, which shows elevated values. The obtained results were compared with other countries and with the worldwide median certified values.